Dinamika Konflik antara Masyarakat Buruh dengan Pengusaha : Studi Kasus Pabrik Ikan di Desa Kedungrejo Kecamatan Muncar dalam Prespektif Teori Konflik Karl Max - Septian Bintang Cahyo; Jovanes Agus Fernanda; Ovie Faiz Pratama (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research explores the dynamics of conflict that occur between workers and factory entrepreneurs in Kedungrejo Village, Muncar District, using the perspective of Karl Marx's conflict icon theory. Fish factories are one of the main economic sectors in this area, and conflicts between fish factory workers and entrepreneurs have a significant impact on the social and economic life of local communities. Karl Marx's conflict theory is used as an analytical framework to understand the root of the problem, the resources being contested, and the role of social class in this conflict. This research includes participatory observation methods, interviews, and document analysis to explore the perspectives of fish factory workers and entrepreneurs. The research results show that the conflict in Kedungrejo Village is related to economic inequality and control of production resources. Workers experience exploitation, low wages and unsafe working conditions, while fish factory entrepreneurs try to maximize their profits. This conflict reflects the conflict between the working class who seek to protect their economic rights and entrepreneurs who prioritize their profits. In the perspective of Karl Marx's conflict theory, this conflict is the result of a structural conflict between the working class (proletariat) and the owners of capital (capitalists). These conflicts reflect fundamental inequalities in the distribution of wealth and power. This research proposes the need for more inclusive and fair solutions in overcoming this conflict, such as collective bargaining, stricter labor regulations, and building awareness of the working class to increase their bargaining power in negotiations with fish factory entrepreneurs. Thus, this research provides insight into the dynamics of conflict between workers and fish factory entrepreneurs in the context of the Kedungrejo Village community, as well as its implications from the perspective of Karl Marx's conflict theory.